PENGARUH ELEKTROLISIS TERHADAP RENDEMEN MINYAK JARAK YANG DIHASILKAN PADA PROSES PEMBUATAN BIODIESEL - Herlian Eriska Putra; Agusta Samodra Putra (Jurnal Kimia Terapan Indonesia, 2011)
The use of jatropha oil as a source of raw material for making biodiesel is needed in order to decrease the production cost of biodiesel, since jatropha oil is categorized as non edible fat. In this research, the biodiesel production process by using an electrochemical reactor has been done. At the beginning of treatment, carried out the hydrolysis of oil by using HrS04 with acid and oil volume ratio is 1: 20. At follow-up treatment, carried out the decarboxylation via electrolysis. This process is done by varying the voltage of 0 V, 10 V,20 V,30 V,the variation of the concentration of 0.5 M acetic acid. 1 M, 1.5 M, as well as the distance between the electrodes in the reactor 5em and 10 em. From the experiments shown that electrolysis with voltage  parameters, acidic electrolyte solution. and electrode spacing affects the yield of decarboxylation process. Electrolysiswith 1.5 M acetic acid concentration and voltage of 30 volts per cent obtained the highest biodiesel yield of compound that is 70.432% in the reactor with inter-electrode distance of 5cm. While in the reactor with inter-electrode distance of 10 cm. thehighest yield was 53.372% by reacting the oil with 1.5 M acetic acid and voltage 30 Volt.Keywords : voltage, decarboxylation, electrolysis, acidconcentration, electrode distance, biodiesel.